2021
DOI: 10.1097/mpg.0000000000003139
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mesenteric Artery Blood Flow in Parenterally Fed Versus Enterally Fed Preterm Infants

Abstract: Objectives: The aim of the study was to compare superior mesenteric artery (SMA) flow in premature infants with parenteral and enteral nutrition. Methods: A prospective study was conducted on 2 groups of preterm infants with gestational age of 280/7 to 366/7 weeks: group 1 did not qualify for early enteral feeds and received parenteral nutrition (PN), and group 2 received early enteral feeding. SMA peak systolic velocity (PSV), end diastolic velocity (EDV), and pulsatility index (PI) were measured using Dopple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Consist with the study [ 39 ], we found initiation of enteral feeding within 3 DOL was a protective factor for developing sIVH. Physiologically, studies showed that early feeding was associated with increased superior mesenteric artery blood flow, and decreased intestinal vascular resistance, which has uncertain association with the occurrence of sIVH [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consist with the study [ 39 ], we found initiation of enteral feeding within 3 DOL was a protective factor for developing sIVH. Physiologically, studies showed that early feeding was associated with increased superior mesenteric artery blood flow, and decreased intestinal vascular resistance, which has uncertain association with the occurrence of sIVH [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%